Young children’s ability to describe intermediate clothing placement - Wylie, Breanne (Child maltreatment, 2021)
Children's ability to adequately describe clothing placement is essential to evaluating their allegations of sexual abuse. Intermediate clothing placement (partially removed clothing) may be difficult for young children to describe, requiring more detailed explanations to indicate the location of clothing (e.g., the clothes were pulled down to the knees). The current study investigated 172 3- to 6-year-olds' descriptions of clothing placement when responding to commonly used questions (yes/no, forced-choice, open-choice, where), as well as children's on-off response tendencies when describing intermediate placement (i.e., labeling the clothing as fully on or off). Results revealed that where questions were superior in eliciting intermediate descriptions, even for the youngest children. Children sometimes exhibited tendencies to describe intermediate placements as "on" or "off", which varied by question-type and clothing placement. The implications of the findings for interviewing young children about sexual abuse are discussed.